Provision of Specialised Services under Regulation (EU) 2015/2120 of the Parliament and of the Council - Totoraitis, Laurynas (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] An opportunity to differentiate data packets by providing priority to specific packets is a precondition required to provide progressive specialised services online. Telecom Single Market Regulation sets conditions to provide specialised services. The conditions are analysed in this article.